An Interview with Robert N. Bellah, July 8, 2013 - Yang, Fenggang (Review of Religion and Chinese Society, 2014)
In this interview, the late Robert Bellah outlines his thoughts on and academic contributions to the study of religion in Chinese Society. Drawing on his extensive experience and knowledge, Dr. Bellah answers a wide range of questions from the role China played in his intellectual endeavors to the role of Confucianism in China, to Sheilaism and civil religion as universal phenomena.